An analytical model of GaAs OPFET - Chakrabarti P.; Gupta A.; Khan N.A. (My University, 2025)
This paper presents an analytical model for determining the d.c. characteristics of GaAs-OPFET (optically controlled field effect transistor). The model takes into account all the major effects that determine the device characteristics in the illuminated condition. Calculations have been carried out for a GaAs-OPFET to examine the effect of illumination on current-voltage characteristics, drain-to-source capacitance (Cds), internal gate-to-source capacitance (Cgs), drain-to-source resistance (Rds) and transconductance (gm). The model takes into account the effect of photo-generation in the semi-insulating substrate region. The semi-insulating nature of substrate has been modeled accurately for the first time. Copyright © 1996 Elsevier Science Ltd.